The effects of economic freedom on FDI inflows: an empirical analysis. Issue 11 (3rd March 2019) - Ghazalian, Pascal L.; Amponsem, Frederick
ABSTRACT: There is a regular emphasis on the significant role of inward Foreign Direct Investment (FDI) in promoting economic growth. This favourable relationship has induced many governments to adopt policies intended to increase FDI inflows and, thereby, to create conducive business and economic conditions for Multinational Enterprises (MNEs). This paper examines the effects of Economic Freedom (EF) and its sub-components reflecting the Quality of Institutions (QIs) on FDI inflows, using indices derived from the Fraser Institute and from the Heritage Foundation. The empirical analysis is carried out for a panel dataset using different econometric methodologies and empirical specifications. The results underline positive effects of EF on FDI inflows. They reveal that EF sub-components have varying impacts on FDI inflows, where rule of law, market openness, and less-restrictive regulatory environment stand out as the major FDI-promoting institutional factors. Also, there is an empirical evidence that the effects of EF sub-components on FDI inflows exhibit variations through the economic characteristics of the host countries and across geo-economic regions. The results suggest that governments should pursue EF-improving policies, which should be tailored according to the economic and geo-economic characteristics of the host countries, to increase FDI inflows.